2021
DOI: 10.1002/anie.202014682
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Noble‐Gas Compounds of Krypton(II) and Xenon(VI); [F5Xe(FKrF)AsF6] and [F5Xe(FKrF)2AsF6]

Abstract: The coordination chemistry of KrF 2 has been limited in contrast with that of XeF 2 ,w hich exhibits af ar richer coordination chemistry with main-group and transition-metal cations.I nt he present work, reactions of [XeF 5 ][AsF 6 ]w ith KrF 2 in anhydrous HF solvent afforded [F 5 Xe(FKrF)AsF 6 ] and [F 5 Xe(FKrF) 2 AsF 6 ], the first mixed krypton/xenon compounds.X-ray crystal structures and Raman spectra show the KrF 2 ligands and [AsF 6 ] À anions are F-coordinated to the xenon atoms of the [XeF 5 ] + cati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…[38] Crystal selection and mounting was carried out at low temperature (about À 50 to À 60 °C) under protective cold nitrogen stream employing a previously described low-temperature crystal mounting procedure. [39] The crystal structures of BF 3 • OC(CH 3 ) 2 and BF 3 • OC(OCH 2 ) 2 measured at 150 K are in good agreement with previously determined structures [24] at 100 K: ], CCDC number: 1972336. [24] BF 3 • OC(CH 3 ) 2 , (P2 1 /n, a = 6.8416(2) Å, b = 14.4962(4) Å, c = 6.9580(2) Å, β = 115.8250(10)°, V = 621.16(3) Å 3 ), CCDC number: 1972338.. [24]…”
Section: Transmission Electron Microscopy and Electron Energy Loss Sp...supporting
confidence: 79%
See 1 more Smart Citation
“…[38] Crystal selection and mounting was carried out at low temperature (about À 50 to À 60 °C) under protective cold nitrogen stream employing a previously described low-temperature crystal mounting procedure. [39] The crystal structures of BF 3 • OC(CH 3 ) 2 and BF 3 • OC(OCH 2 ) 2 measured at 150 K are in good agreement with previously determined structures [24] at 100 K: ], CCDC number: 1972336. [24] BF 3 • OC(CH 3 ) 2 , (P2 1 /n, a = 6.8416(2) Å, b = 14.4962(4) Å, c = 6.9580(2) Å, β = 115.8250(10)°, V = 621.16(3) Å 3 ), CCDC number: 1972338.. [24]…”
Section: Transmission Electron Microscopy and Electron Energy Loss Sp...supporting
confidence: 79%
“…Hydrogen atoms were freely refined including an isotropic thermal parameter [38] . Crystal selection and mounting was carried out at low temperature (about −50 to −60 °C) under protective cold nitrogen stream employing a previously described low‐temperature crystal mounting procedure [39] …”
Section: Methodsmentioning
confidence: 99%
“…[9] The NgÀ F bonds of the NgF 2 ligand become more polarized, consistent with the calculated FIAs of the Group 6 oxide tetrafluorides (CrOF 4 , À 285; MoOF 4 , À 355 WOF 4 , À 386 kJ mol À 1 ), [12] which ). [9] Similar trends have been noted for other terminally coordinated NgF 2 (Ng = Kr, Xe) adducts: [F 2 OBr (FNgF) 2 AsF 6 ], [13,14] [Mg(FKrF) 4 (AsF 6 ) 2 ], [15] [F 5 Xe(FNgF) n AsF 6 ] (n = 1, 2), [16,17] and [Hg(FKrF) 8 ][AsF 6 ] 2 . [18] The MoÀ O (Kr, 1.6508( 12 3) Å) bond lengths are comparable to those of the infinite-chain MoOF 4 [19] and tetrameric WOF 4 structures, [20] and gaseous monomeric MOF 4 (Mo, [21] W [22] ).…”
Section: X-ray Crystallographysupporting
confidence: 69%
“…The F−Kr−F bond angles are near‐linear (178.3(2)–179.19(5)°), and are comparable to those of NgF 2 ⋅ CrOF 4 (Kr: 179.91(5)°; Xe: 179.1(1), 179.81(8)°), [9] The Ng−F b ‐ ‐ ‐M bond angles in KrF 2 ⋅ MOF 4 (Mo, 134.33(5); W, 135.22(12)°) and XeF 2 ⋅ MOF 4 (Mo, 148.09(7); W, 150.6(2)°) are bent and are in good agreement with those of NgF 2 ⋅ CrOF 4 (Kr: 123.51(4)°; Xe: 133.1(1), 118.50(8)°) [9] . Similar trends have been noted for other terminally coordinated NgF 2 (Ng=Kr, Xe) adducts: [F 2 OBr(FNgF) 2 AsF 6 ], [13,14] [Mg(FKrF) 4 (AsF 6 ) 2 ], [15] [F 5 Xe(FNgF) n AsF 6 ] ( n =1, 2), [16,17] and [Hg(FKrF) 8 ][AsF 6 ] 2 [18] …”
Section: Resultsmentioning
confidence: 81%
“…12 Remarkably, mixed noble gas compounds of Kr(II) and Xe(VI) were reported recently, which significantly extend the limited chemistry of krypton. 13 The stabilization of more challenging noble gas species has only been accomplished under low-temperature environments, in high pressure devices, or in the isolated conditions of the gas phase. 1,2,[14][15][16][17][18] Several gas-phase studies were reported over the years involving SF 6 and the noble gases.…”
Section: Introductionmentioning
confidence: 99%